199 years of Parkinson disease – what have we learned and what is the path to the future?. (31st August 2016) - Schulz, Jörg B.; Hausmann, Laura; Hardy, John
Abstract : In 1817, 199 years ago, James Parkinson described for the first time in 'An Essay on the Shaking Palsy' the symptoms of the disease that was later named Parkinson Disease. The current special issue of the Journal of Neurochemistry is dedicated to the discoveries and advances that have been made since, leading to a better understanding of this neurodegenerative disease and of potential treatment options. Reputed researchers cover various aspects from neuroanatomical basics; genetic and molecular risk factors such as LRRK2; the available cell and animal models that mimic crucial features of the pathophysiology; to clinical aspects and treatments, including deep brain stimulation. This article is part of a special issue on Parkinson disease . Abstract : In 1817, 199 years ago, James Parkinson described for the first time in 'An Essay on the Shaking Palsy' the symptoms of the disease that was later named Parkinson Disease. The current special issue of the Journal of Neurochemistry is dedicated to the discoveries and advances that have been made since, leading to a better understanding of this neurodegenerative disease and of potential treatment options. Reputed researchers cover various aspects from neuroanatomical basics; genetic and molecular risk factors such as LRRK2; the available cell and animal models that mimic crucial features of the pathophysiology; to clinical aspects and treatments, including deep brain stimulation. This article is part of a special issue on Parkinson disease .